Efisiensi Penggunaan Input Produksi Kakao Di Desa Dolago Kecamatan Parigi Selatan Kabupeten Parigi Moutong - Sarini Sarini (Mitra Sains, 2017)
Central Sulawesi Province especially Parigi Moutong district, the majority of the population lives on farming, so to obtain optimal production requires the use of efficient input. The purpose of this research is to determine the effect of cocoa production inputs (the number of trees in production (X1), Urea fertilizer (X2), NPK fertilizer (X3) and labor (X4) that affecting the level of cocoa production efficiency. The respondent was selected through Simple Random Sampling that obtained 35 out of 350 people of total population. The analysis used is Multiple Linear Regression using Cobb-Douglass and Efficiency Analysis. The results of F-test show that variable the number of cocoa trees produced (X1), Urea fertilizer (X2), NPK fertilizer (X3) and labor (X4) simultaneously affect the cocoa production at Dolago Village. The result of test-t show that variable of the number of cocoa trees produces (X1), Urea fertilizer (X2), NPK fertilizer (X3) and labor (X4) affecting the production of cocoa at Dolago Village. The results of the efficiency analysis show that the value of variable efficiency (The number of trees in production (X1) 0.26<1 it means no need the addition of cocoa trees, the value of the variable urea fertilizer efficiency (X2) 1.24>1 it means not efficient, need the addition of urea fertilizer in accordance with a balanced dose, the value of the variable NPK fertilizer (X3) 463.8>1 it means that the use of input NPK fertilizer not efficient so that need increasing doses of NPK fertilizer in accordance with the dose of balanced and the value of the variable efficiency of labor (X4) 0.066<1 it means not efficient because the use is excessive so farmers had to reduce the use of labor on cocoa farms at Dolago village, South Parigi sub district.